Przywództwo skuteczne - przykład opatrzony komentarzem - Kłos, Zbigniew (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the paper the issue of successful leadership is considered. The problem is analyzed based on the example of the experienced CEO from one of the leading Polish middle size enterprises. The fundamental elements of his leadership characteristics are reviewed and the main conditions of leadership attitude shaping are searched. The paper ends with some personal reflections dealing with the face-to-face meetings with the earlier mentioned CEO. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 98-107